Pengaruh Disipilin Penerapan Anggaran Produksi Terhadap Tingkat Capaian Realisasi Produksi Pada PT. Jaya Semesta - ., Heny; S, Tarida Marlina (Jurnal Ilmiah Akuntansi Kesatuan, 2016)
In the implementation of a company's production process, the production budget is something that should not be overlooked. Production budget discipline will create both in terms of production control units and control costs including raw materials, direct labor control, and factory overhead cost control. Thus, the production process will be coordinated and run in accordance with company objectives. Based on this assumptions, this research tries to examine whether there are differences between the actual production budget both in terms of production volumes and costs, as well as to determine whether there is influence between the production budget discipline on the level of achievement of the actual production. Research conducted in PT. Jaya Semesta located at Jl. 6 Coral Tamarind Western Hero, Coventry - Bogor. PT. Jaya Semesta is a company engaged in manufacturing electrical components. The results showed that the production budget at PT. Jaya Semesta in preparing the production budget of the company using the combined methods of Top Down and Buttom up. Production budget PT. Jaya Universe in 2012 is not effective (discipline), it is evidents from the budgeted volume with the volume produced has a percentage difference of 13% (thirteen percent), which is far higher than the tolerances specified by the company and the budgeted overhead costs overhead costs produced has a difference of 7% (seven percent) above the tolerance limits set by the company in the amount of 5% (five percent). Whereas in 2013 the production budget PT. Jaya Semesta is concluede to be effective (discipline) as a means of controlling production, budgeted volume with the volume produced has a percentage difference of 1% (one percent) and the costs incurred by the company adhere to the budgets that have been defined where production expenses below the specified tolerance company, this would be beneficial for the company and in terms of quality, product switch BG 802 rarely experienced level of disability, the maximum level of disability produced by 2%. With the value of the average deviation decreased from the year 2012 to the year 2013, PT. Jaya Semesta in preparing the production budget of the switch BG802 more focused towards the target (destination) to implement a production budget discipline (effective and efficient). Evaluation results in this study show that the controlled production budget is the key to success in the overall production process. It can be concluded that the proper preparation of production budget is necessary because the budget can assess the efficiency and effectiveness of a company.